Fabrication of 3D Graphene and 3D Graphene Oxide Devices for Sensing VOCs. Issue 19 (24th February 2016) - Matsuyama, So; Sugiyama, Tomoaki; Ikoma, Toshiyuki; Cross, Jeffrey S.
ABSTRACT: Detection of volatile organic compounds (VOCs) emitted from cancerous tumor cells in exhaled human breath allows for early diagnosis of various types of cancers. 3D graphene with a large surface area is considered a suitable material for creating novel sensitive VOCs sensors. In this study, 3D graphene and 3D graphene oxide were synthesized from graphene oxide suspension, hydroquinone and formaldehyde by employing polymerization and reduction. The capability of VOC gas sensing was evaluated by measuring the electrical current response in flowing N2 gas over a range of concentrations of acetone or 1-butanol at room temperature. It was observed that the device current correlated well with the VOC concentration. The adsorption of acetone decreased the current, but the adsorption of 1-butanol increased the current during sensing. 3D graphene oxide device was more sensitive than 3D graphene device because of the high concentration of oxygen-containing functional groups on the surface. These results indicated that 3D graphene and 3D graphene oxide may be the suitable materials for VOCs sensing devices.